2018
DOI: 10.3390/polym10010056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on the Mechanical Properties and Reactive Behavior of Al-PTFE under Quasi-Static Compression

Abstract: Al-PTFE (aluminum-polytetrafluoroethylene) is a typical kind of Reactive Material (RM), which has a variety of potential applications in weapon systems. In this paper, quasi-static compression experiments were carried out for a pressed and sintered mixture of Al and PTFE powders using a microcomputer-controlled electronic universal testing machine. The results show that both the mechanical property and reactive behavior of Al-PTFE are strongly temperature-dependent. The material undergoes a brittle-ductile tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Before, proceeding for Tensile testing, an EDS mapping of fabricated composite is performed, to ensure the best possible distribution of basic element of components [ 18 ], as shown in Figure 2 . It can be seen that the major components, carbon (C), calcium (Ca), silicon (Si), are homogeneously distributed, so that there are no aggregates and there is no site in the matrix, left unreinforced.…”
Section: Methodsmentioning
confidence: 99%
“…Before, proceeding for Tensile testing, an EDS mapping of fabricated composite is performed, to ensure the best possible distribution of basic element of components [ 18 ], as shown in Figure 2 . It can be seen that the major components, carbon (C), calcium (Ca), silicon (Si), are homogeneously distributed, so that there are no aggregates and there is no site in the matrix, left unreinforced.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this discovery, the impact exerted by sintering temperature, component ratio and Al particle size on the quasi-static reaction of Al/PTFE were investigated. Wang et al 15 studied the effect of temperature on the mechanical properties and reactive behavior of Al/PTFE under quasi-static compression. Scanning electron microscopy results showed that the temperature played a very momentous role in the fracture mechanisms of PTFE.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the PTFE/Al composite the PTFE polymer plays a dual role of strengthening and toughening of the composite. The PTFE/Al composite exhibit a gradual change from brittleness to ductility with increasing temperature due to the enhanced PTFE deformation [ 24 ]. Remarkably, the minimum specific incident energy that causes ignition of the composite reduces by 58% when the temperature is raised from 22 °C to 205 °C.…”
Section: Reactive Structures Based On Fluoropolymer-based Bindersmentioning
confidence: 99%